Promotional Strategy for Magic Group Media - Melia Lohanjaya (Jurnal Desain Komunikasi Visual Nirmana, 2018)
Magic Group Media is a post-production company based in Amsterdam. Magic Group Media constantly keeps growing and being ambitious in a way to expand the business and target a wider market. Magic has already done some promotion strategies before, but to reach a bigger market, Magic evaluates it is essential to invest more in effective promotional strategy. Through this promotional strategy, Magic wants to build a working relationship with new potential clients. This study is aimed at analyzing and knowing what promotional strategy can be used by Magic Group Media to build a working relationship with potential clients.